Experience of professional training of specialists in the field of education and information technologies of the Department of Informatics and Cybernetics - Viacheslav Osadchyi (Ukrainian Journal of Educational Studies and Information Technology, 2017)
The paper, which is based on the analysis of scientific and methodological works of the Department of Informatics and Cybernetics of Bogdan Khmelnitsky Melitopol state pedagogical university, describes the experience of professional training of specialists in the field of education and information technologies in such specialties as «Computer Science», «Secondary Education. Informatics» and «Professional education. Computer Technology». It is concluded that during the last decade, scholars of the department have developed numerous scientific works: Ph.D. and doctoral dissertations, monographs, educational and teaching aids. The most current attention of the teachers, post-graduate students and doctoral students of the department is directed to problems of professional training of future teachers of informatics and future software engineers, as well as the substantiation and introduction of information and communication technologies to pedagogical education. In particular, the experience for solving problems of different initial level of knowledge and skills in information technology of future IT teachers is presented in the works of H. V. Briantseva, solving the problem of the insufficient level of technological culture of future computer science teachers is presented in papers of S. M. Pryima the formation of professional competence for future computer science teachers in the process of studying professional disciplines is performed in works of K. P. Osadcha, the formation of media competence for future teachers of informatics in pedagogical universities is described in papers of І. М. Naumuk V. V. Osadchyi has studied the issue of the substantiation and practical implementation of information and communication technologies in the training of future teachers. Different aspects of professional training ofr future software engineers are researched in the works of such scholars of the department as V. S. Kruhlyk, V. V. Osadchyi, S. V. Sharov, V. S. Eremeev and others.